Lead(II) Ion Selective Electrode with PVC Membrane Based on 5,5’-Dithiobis-(2-Nitrobenzoic Acid) as Membrane Carrier - Li, Song; Zhou, Yuanyuan (Asian Journal of Chemistry, 2011)
The characteristics of PVC membrane for lead(II) ion-selective electrode based on 5,5'-dithiobis-(2-nitrobenzoic acid) as carrier was studied. The electrode displays an excellent Nernstian response for Pb2+ over a wide concentration range (1.0 × 10-5 1.0 × 10-2 M). It has a rapid response time and can be used for at least 3 months without any divergence in potentials. The proposed electrode revealed good selectivities for Pb2+ over a wide variety of other metal ions in a pH range of 2.2- 7.0. It was used as an indicator electrode in potentiometric titration of sulfate ions with a lead ion solution.